PROCEDURE FOR CALCULATING THE RELIABILITY OF RESERVED SYSTEMS - Azarskov, V. N.; Jassim , Mohammed Kasmi; Strelnikov , V. P. (Problems of Informatization and Control, 2021)
A method is proposed and a technique for calculating the reliability of parallel systems with a loaded reserve is developed, which leads to the determination of the distribution function (DM-distribution) of the operating time to failure of the systems under consideration, on the basis of which one can simply obtain estimates of all.